Utilization of Moringa Leaves as an Alternative Source of Food Loaded with Nutrition in Making Family Food in Kelurahan Pasir Nan Tigo Kecamatan Koto Tangah Kota Padang - Melindra wanda Mulia (Pelita Eksakta, 2020)
This community service was carried out at the request of mothers’ gathering group (PKK) in Kelurahan Pasir Nan Tigo, Kecamatan Koto Tangah, Padang. The aims of this activity were sharing knowledge and giving training on cheap and economical nutrient-laden food in order to improve family nutrition and to help society to do entrepreneurship. Team from department of chemistry UNP in particular gave material on the benefits of Moringa and the production of its use. The activity began with material presentation by the speakers, followed by practice. Pre and post knowledge of participant on content, benefits, and maximum use of Moringa leaves for food were analyzed. Data collected through questionnaires and observation showed that participant agreed to the use of Moringa leaves. Business opportunities of Moringa leaves processes are promising because resources required are small; tools to process Moringa are available; there is market target that supports the business; and business competition of Moringa leaves is quite low. Participant knows the basis for good processing of Moringa leaves. Also, participants knowledge and skills about Moringa leaves and its preparations have increased.